Fifteen years of research on PISA effects on education governance: A critical review - Pons, Xavier (European Journal of Education, 2017)
This article provides a literature review on the effects of the OECD's Programme for International Student Assessment (PISA) on education governance and policy process across participating countries. This review seemed necessary because there has been a growing body of literature on this topic since 2003, especially since 2010, because this literature is not always well-known and because the discourse on the so-called ‘PISA shock’ remains important, even if it is more of a metaphor than a concept and may be politically partial. The article exploits a dataset of 87 references which show that PISA introduced major changes in the governance of education worldwide. Driven by soft power strategies and new policy transfers, this governance is based on data and measurement tools which redefine the scales of education policies. It also shows that PISA has a strong influence on a variety of national reforms, as illustrated in many case studies. However, this influence strongly depends on domestic policy contexts that scholars intended to capture through different theoretical frameworks. Nonetheless, few propose overarching theorisations of the political meaning of PISA effects on education governance and policy processes. The article concludes by stressing three main challenges for the subsequent studies on these PISA effects: better conceptualising these effects, preserving an epistemology of uncertainty in order to avoid taken for granted views and normalising the research on PISA effects not to perpetually and artificially rediscover its so-called novelty.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ejed.12213
Keywords: OECD; PISA; education policy; globalisation; governance; survey